KONSEP DAN STRATEGI KOMUNIKASI PEMASARAN: PERUBAHAN PERILAKU KONSUMEN MENUJU ERA DISRUPSI - Dea Farahdiba (Program Studi Ilmu Komunikasi FBIK Unissula, 2020)
Marketing has evolved from the concept of marketing 1.0 to 4.0 so that to learn what is needed and wanted by consumers, marketers must be able to have policies using appropriate communication so that various information about products can be transferred to consumers. For this reason, it is necessary to better understand communication, especially marketing communication in terms of shaping consumer behavior. The purpose of this article is to provide insight in the field of marketing communication. This research methodology is a literature study from several journals that discusses marketing communication. The existence of communication can make it easier for someone to interact between one individual with another individual. Without communication there is no human life process. That is, every human being needs communication to exchange ideas in order to realize what he wants. Three major marketing shifts, marked by product-driven marketing in the later 1.0 era towards customer-centered marketing in the 2.0 era. Human-centered marketing existed in the 3.0 era. On the other hand, marketing communication tools can be in the form of advertisements, sales, signage, shops, displays, packaging, free product samples, coupons, giveaway and more. As for changing consumer behavior that is increasingly developing, the impact of marketing 4.0 also results in viral marketing through social networks such as Facebook enabling continuous two-way interactivity from anywhere and at any time.